2005
DOI: 10.1007/s11102-005-3328-x
|View full text |Cite
|
Sign up to set email alerts
|

Sellar Neuroblastoma Mimicking Pituitary Adenoma

Abstract: Neuroblastoma should be considered in the differential diagnosis of patients with sellar lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…2) Furthermore, there have been two additional suggestions for the origin of the tumor:neuronal transformation from the pituitary epithelium, and a ganglion of Locy which grows between the olfactory fossa and the telencephalic vesicle. 1,4,6,8,9) Oyama et al reported the case of a 33-year-old male with sellar neuroblastoma who did not display an elevated urinary VMA. In this case, they suggested that the primary tumor could have arisen in the supradiaphragmatic region and extended into the sellar turcica, since catecholamine metabolites in the urine are usually elevated in peripheral neuroblastoma but not within tumor of the blood-brain barrier: primary cerebral neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Furthermore, there have been two additional suggestions for the origin of the tumor:neuronal transformation from the pituitary epithelium, and a ganglion of Locy which grows between the olfactory fossa and the telencephalic vesicle. 1,4,6,8,9) Oyama et al reported the case of a 33-year-old male with sellar neuroblastoma who did not display an elevated urinary VMA. In this case, they suggested that the primary tumor could have arisen in the supradiaphragmatic region and extended into the sellar turcica, since catecholamine metabolites in the urine are usually elevated in peripheral neuroblastoma but not within tumor of the blood-brain barrier: primary cerebral neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, they suggested that the primary tumor could have arisen in the supradiaphragmatic region and extended into the sellar turcica, since catecholamine metabolites in the urine are usually elevated in peripheral neuroblastoma but not within tumor of the blood-brain barrier: primary cerebral neuroblastoma. 4) …”
Section: Discussionmentioning
confidence: 99%
“…NeuroD1 is ubiquitously expressed in the nuclei of neoplastic cells (e, ABC/peroxidase ×10). Some neoplastic cells exhibit expression of anti-diuretic hormone (f, ABC/peroxidase ×20) signs and symptoms of mass effect [1][2][3][4][5][14][15][16][17]. No patients presented with SIADH although one patient showed hyponatraemia reportedly due to extra-cranial causes [5].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases including ours, surgery was challenging because of extensive infiltration of the surrounding structures. Seven patients were free of disease between 1 and 5 years after surgery while one patient experienced several recurrences and eventually, the tumour metastasized to the cervical spine 3 years following the initial operation [2]. Given the sheer rarity of SNB and the short follow-up of the published cases, it is difficult to establish if the outcome of SNB is similar to the more common ONB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation